Nomenclatural notes in the Pleurothallidinae (Orchidaceae): miscellaneous part II - Karremans, Adam P.; Rojas-Alvarado, Gustavo; Bezerra-Silva, Luiz Eduardo; Flores-Rojas, Jeffrey; Murillo-Murillo, Jose Martín; Romero-Ceciliano, Marysol; Segura-Bermúdez, Oscar A. (Phytotaxa, 2021)
Nomenclatural changes and notes are provided for genera in subtribe Pleurothallidinae (Epidendroideae: Orchidaceae) to comply with the International code of nomenclature for algae, fungi, and plants. The proposed changes include new names and combinations, author citations, spelling and synonymy. Brief notes are also provided.